Variability, trait relationship and path analysis for seed yield and seed quality parameters in Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
Forty accessions of Indian mustard (Brassica juncea L.) germplasm evaluated for yield as well as quality traits revealed significant differences among the accessions for seed yield contributing traits and seed quality parameters. The highest estimate of phenotypic and genotypic coefficient of variation was found for secondary branches per plant, harvest index. Higher estimates of heritability coupled with higher genetic advance was observed in harvest index and secondary branches per plant. The seed yield per plant, the most important economic trait, was positively and significantly correlated with 1000-seed weight, harvest index, number of seeds per at both genotypic and phenotypic levels. The characters showing significant positive correlation among yield and important characters would be highly effective and efficient in improving respective traits. Path coefficient analysis identified as plant height and 1000-seed weight important component having high order of direct effect and seedling dry weight via vigour index-II and seedling length via vigour index-II important component having high order of indirect effect on seed yield per plant. The characters identified above as important direct and indirect yield components merit due to consideration in formulating effective selection strategy for developing high yielding mustard genotypes. These components plays an important role in a crop for best selecting of genotypes for making rapid improvement in yield and other desirable characters as well as to select the potential parent for hybridization programmes.